2016
DOI: 10.1074/jbc.m116.718668
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatically Inactive Procaspase 1 stabilizes the ASC Pyroptosome and Supports Pyroptosome Spreading during Cell Division

Abstract: Caspase-1 is a key player during the initiation of pro-inflammatory innate immune responses, activating pro-IL-1␤ in socalled inflammasomes. A subset of patients with recurrent febrile episodes and systemic inflammation of unknown origin harbor mutations in CASP1 encoding caspase-1. CASP1 variants result in reduced enzymatic activity of caspase-1 and impaired IL-1␤ secretion. The apparent paradox of reduced IL-1␤ secretion but systemic inflammation led to the hypothesis that CASP1 mutations may result in varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 54 publications
2
15
0
Order By: Relevance
“…When only ASC is expressed, the diameter of ASC specks is larger, at ∼5 mm. Thus, ICCE can be used to evaluate speck area and diameter in a high-throughput system, yielding quantitative results similar to those reported by others (41,42). These changes in speck area suggest a possible higher order organization of the speck upon NLRP3 activation and implicate NLRP3 activation in dictating features of such organization (Fig.…”
Section: Calculation Of Asc Speck Areasupporting
confidence: 84%
See 2 more Smart Citations
“…When only ASC is expressed, the diameter of ASC specks is larger, at ∼5 mm. Thus, ICCE can be used to evaluate speck area and diameter in a high-throughput system, yielding quantitative results similar to those reported by others (41,42). These changes in speck area suggest a possible higher order organization of the speck upon NLRP3 activation and implicate NLRP3 activation in dictating features of such organization (Fig.…”
Section: Calculation Of Asc Speck Areasupporting
confidence: 84%
“…ICCE can also be used for qualitative assessment of ASC speck features such as area, which is not possible using TOFIE. Variations in ASC speck size have recently been associated with the presence of active caspase-1 and the duration of caspase-1 activity (41,42). Further, in the absence of NLRP3, hypotonic conditions lead to ASC speck formation without caspase-1 activation (45), reminiscent of the specks formed when ASC is overexpressed (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports showed that 1) protease-dead mutant of pro-caspase-1 can still be translocated to the nucleus [ 31 ], suggesting that pro-caspase-1 may travel to nucleus for its enzymatic activities-independent functions such as promotion of gene transcription as we reported [ 28 ]; and 2) enzymatically inactive pro-caspase-1 stabilizes the apoptosis-associated speck-like protein containing a CARD (ASC, PYCARD) pyroptosome (a supramolecular assembly of ASC dimers mediating inflammatory cell death via caspase-1 activation [ 88 ]) and supports pyroptosome spreading during cell division [ 89 ]. We then hypothesized that LPC modulate RNA transcriptomes in HAECs in the presence and absence of caspase-1 inhibitor ( Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Whether the ASC speck is a SMOC that facilitates the formation and release of small inflammasome complexes is unclear and demonstrating this presents numerous challenges. ASC specks are larger in cells with enzymatically inactive caspase-1 (Caspase-1 DEAD) compared to cells with wildtype caspase-1 (Stein et al, 2016). Moreover, ASC specks formed by ASC alone are larger than NLRP3:ASC specks and the size of NLRP3:ASC specks is further reduced after nigericin stimulation (Nagar et al, 2019).…”
Section: The Speck Lowers the Agonist Threshold Of For Nlrp3 Inflammasome Activationmentioning
confidence: 99%